Strategi Pembelajaran Konstruktivisme Guru PAI dalam Meningkatkan Akhlakul Karimah di MI Miftahuddiniyah Bekasi - Sukeni (4, 2026)
This study aims to analyze the constructivist learning strategies implemented by Islamic Religious Education (PAI) teachers to improve students' moral character at MI Miftahuddiniyah Bekasi. The research background stems from the need for modern education to develop learning models that focus not only on academic achievement but also on strengthening students' morals and character. The constructivist approach is considered relevant because it encourages students to build understanding through direct experience, reflection, social interaction, and active involvement in the learning process. This study used a qualitative approach with descriptive methods. Data were collected through observations of learning activities, in-depth interviews with PAI teachers, madrasah principals, and students, and documentation of the school's habituation program. Data analysis was conducted through the stages of data reduction, presentation, and drawing conclusions. The results show that PAI teachers implement constructivist strategies through various steps, such as problem-based learning, group discussions, moral case studies, role-playing, and the instilling of moral habits in daily activities. The integration of Islamic values ​​is carried out in an applicable and contextual manner, enabling students to understand religious teachings more meaningfully. This approach has been proven to have a positive impact on improving students' role models, moral awareness, discipline, and social attitudes. Research concludes that constructivist learning strategies significantly contribute to developing students with noble, critical, and integrity-based character. This model not only builds cognitive intelligence but also fosters sustainable spirituality and good morals. These findings serve as recommendations for Islamic educational institutions to implement a constructivist approach to strengthen character education in the modern era. Abstrak Penelitian ini bertujuan untuk menganalisis strategi pembelajaran konstruktivisme yang diterapkan oleh Guru Pendidikan Agama Islam (PAI) dalam meningkatkan akhlakul karimah peserta didik di MI Miftahuddiniyah Bekasi. Latar belakang penelitian berangkat dari kebutuhan pendidikan modern untuk mengembangkan model pembelajaran yang tidak hanya fokus pada capaian akademik, tetapi juga penguatan moral dan karakter siswa. Pendekatan konstruktivisme dipandang relevan karena mendorong siswa membangun pemahaman melalui pengalaman langsung, refleksi, interaksi sosial, serta keterlibatan aktif dalam proses belajar. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi kegiatan pembelajaran, wawancara mendalam dengan guru PAI, kepala madrasah, dan peserta didik, serta dokumentasi program pembiasaan di sekolah. Analisis data dilakukan melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru PAI menerapkan strategi konstruktivistik melalui berbagai langkah, seperti pembelajaran berbasis masalah, diskusi kelompok, studi kasus moral, role playing, serta pembiasaan akhlak dalam kegiatan sehari-hari. Integrasi nilai-nilai Islam dilakukan secara aplikatif dan kontekstual, sehingga siswa mampu memahami ajaran agama secara lebih bermakna. Pendekatan ini terbukti berdampak positif pada peningkatan keteladanan, kesadaran moral, kedisiplinan, dan sikap sosial siswa. Penelitian menyimpulkan bahwa strategi pembelajaran konstruktivisme memberikan kontribusi besar dalam membentuk peserta didik yang berkarakter mulia, kritis, dan berintegritas. Model ini tidak hanya membangun kecerdasan kognitif, tetapi juga menumbuhkan spiritualitas dan akhlakul karimah yang berkelanjutan. Temuan ini menjadi rekomendasi bagi lembaga pendidikan Islam untuk menerapkan pendekatan